Antioxidant and Iron-Chelating Activity of Some Thai Medicinal Plants - นาใจคง ธวัชชัย; หวันยาวา อาซีด; เก้าเอี้ยน กฤตพงษ์; คงสุขนิรันดร์ จตุพร; ศุภธีรสกุล สนั่น; วงศ์นาวา มาลินี; บํารุงวงศ์ นิสิตา (KKU Science Journal, 2014)
This study aims to investigate the antioxidant and iron-chelating activity of the ethanolic extract from some Thai herbs used to treat patients with blood disorders; Artocarpus heterophyllus Lam, Randia siamensis Craib., Tarenna hoaensis Pit., Plumbago indica L., Alternanthera bettzickiana Standl., Madhuca pierrei H.J.Lam, Aegle marmelos Correa, Plumeria obtusa Woodson and Cinnamomum bejolghota (Buch.-Ham.) Sweet. It was found that C. bejolgnota shows the highest DPPH scavenging activity with the IC50 of 0.06 mg/mL and total flavonoid content of 270.05±15.84 mg catechin equivalence/g extract. R. siamensis shows the highest iron chelating activity with IC50 0.39 mg/mL. The highest total phenolic content was found in A. heterophyllus at 457.00±49.06 mg gallic acid equivalence/g extract. It is noted that the radical scavenging capacity of the extracts correlate with total phenolic content and flavonoid content. However, iron-chelating activity does not correlate with the antioxidant activity, total phenolic content or flavonoid content. The results from this study support the use of these medicinal plants for the treatment of blood disorders in Thai Traditional Medicine.